Seasonal workers in Mediterranean agriculture: The social costs of eating fresh by Jörg Gertel and Sarah Ruth Sippel (Eds.) - Anelyse Margaret Weiler (Canadian Food Studies, 2015)
One of the most common justifications for maintaining low-paid, precarious conditions for farm workers is that while farmers are being squeezed by globalized competition, economic turmoil and increasingly unpredictable weather patterns, labour remains one of the few costs they can control. This lends a Thatcherian logic of “no alternative” to the expanding complexes of seasonal labour migration, which mobilize workers from economically marginalized regions of the world to orchards, fields, and greenhouses in wealthier nations. Seasonal Workers in Mediterranean Agriculture compellingly portrays how migrants bear the harshest costs of procuring year-round fresh fruits and vegetables for a privileged few. While giving voice to the social inequality that fuels the dominant agri-food system, the authors aim to show how the stretching of growing seasons and national borders has made room for new forms of insecurity and profitability.